Mobile devices for the development of critical thinking in the learning of differential equations (2019)
The purpose of this research was to establish a relationship between mobile devices and the development of critical thinking in students of the differential equations subject. The research had a quantitative and qualitative methodological approach with quasi-experimental design, the sample was 110 students. Results: The integration of mobile applications favored and motivated the learning of the applications of differential equations, where the student develops critical thinking at the moment that creates, discovers, imagines and assumes. At the same time, when interacting with colleagues, it implements autonomous and collaborative learning, with the ease of access to information. Conclusion: Regarding the perception of students about this tool, 40% highlight its usefulness in understanding the topics and 51.2% step by step methodology. The average age of the students was 20 years with a standard deviation of 2.01 years.